MEMAHAMI PENGALAMAN PENGAMBILAN KEPUTUSAN REMAJA BERMAIN JUDI ONLINE “SLOT” - Raghabendra, Octova; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Deviant behavior among adolescents in the form of gambling practices has become a compelling area of research, driven by the influence of technological advancements, particularly the internet, which serves as a medium for gambling practices and leads to the phenomenon of online gambling. Negative phenomena such as online gambling, especially slot gambling, are increasingly prevalent among teenagers. This study aims to understand the decision-making experiences of adolescents in engaging in online slot gambling. Using a qualitative approach and Moustakas' analysis method, the research seeks to explore how adolescents experience making decisions to participate in online slot gambling and give meaning to the phenomenon. This study was conducted with four informants, consisting of two males and two females, who are teenagers and active online slot gamblers. The findings indicate that all four informants have decision-making experiences influenced by their psychological conditions, which are enticed by the rewards of slot gambling, as well as by their social environment. This aligns with the aspects of communication that encourage individuals to make decisions, specifically the social and psychological aspects of communication.